PERSPEKTIF EKONOMI ISLAM ATAS PERILAKU KONSUMTIF - Siti Nur Jami’uswaniyah; Eny Latifah (JISEF : Journal Of International Sharia Economics And Financial, 2023)
The purpose of this study was to determine the Islamic economic perspective on consumptive behaviour for students Islamic boarding school. This research method is qualitative descriptive with the type of case study. The results of the research are the consumptive behaviour of female students of Tarbiyatut Tholabah Islamic Boarding School in the perspective of Islamic economics is in accordance with the principles of Islamic economics, namely the principle of justice, the principle of cleanliness, the principle of simplicity, the principle of generosity, and the principle of morality. First, female students in consuming everything always consider its halal, female students also share and maintain mutual harmony among female students. Second, female students in maintaining cleanliness well. Third, female students in their consumptive activities have not been able to apply simplicity, because there are still female students who like to wear branded clothes. As for food, they still often deliv food from outside, because of the temptation of friends. Fourth, female students have a generous helping nature, when there are friends who have not been sent money by their parents, they lend them, share food with each other. Fifth, female students have made rules of order and obligations for female students in the boarding school.